2022
DOI: 10.3390/ijerph191811456
|View full text |Cite
|
Sign up to set email alerts
|

Fully Digital versus Conventional Workflows for Fabricating Posterior Three-Unit Implant-Supported Reconstructions: A Prospective Crossover Clinical Trial

Abstract: This study assessed the clinical variables influencing the success of three-unit implant-supported fixed dental prostheses (ISFDPs) fabricated using either fully digital or conventional workflows. The clinical trial evaluated 10 patients requiring three-unit ISFDPs in the posterior mandible. Maxillomandibular relation records, and digital and conventional impressions were obtained from each patient using an intraoral scanner (IoS) and polyvinylsiloxane (PVS), and the frameworks were fabricated using zirconia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Finally, it is essential to note that the success of any dental treatment depends not only on the technical aspects but also on the patient’s satisfaction [ 22 , 23 , 24 , 25 , 26 , 27 ]. Therefore, thoroughly discussing the patient’s expectations and desires before initiating any treatment is crucial to ensure the desired outcome [ 28 , 29 , 30 , 31 , 32 ]. In this case, the patient was highly satisfied with the final outcome and reported a significant improvement in her self-confidence and overall satisfaction with her smile.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is essential to note that the success of any dental treatment depends not only on the technical aspects but also on the patient’s satisfaction [ 22 , 23 , 24 , 25 , 26 , 27 ]. Therefore, thoroughly discussing the patient’s expectations and desires before initiating any treatment is crucial to ensure the desired outcome [ 28 , 29 , 30 , 31 , 32 ]. In this case, the patient was highly satisfied with the final outcome and reported a significant improvement in her self-confidence and overall satisfaction with her smile.…”
Section: Discussionmentioning
confidence: 99%
“…Benefits in patient preference, time savings and elimination of physical storage make digital workflows superior to conventional dental workflows (Mangano et al, 2017). Accuracy of both intraoral scanners and conventional impression methods are also comparable (Afrashtehfar et al, 2022;Hashemi et al, 2022). Device fabrication via CAD/CAM methods allows for the time efficient production of dental devices (van Noort, 2012).…”
Section: Advances In Mandibular Advancement Splint Fabricationmentioning
confidence: 99%
“…Chairside computer-aided design and computer-aided manufacturing (CAD-CAM) permits clinicians to precisely manufacture a wide array of materials, for provisional or definitive restorations, faster than the traditional methods. [1][2][3][4][5][6][7] Recent studies have demonstrated that CAD-CAM restorations have a better marginal adaptation than conventionally fabricated indirect restorations. 8,9 Similar to CAD-CAM complete cov-erage restorations, laminate veneers (LVs) can be fabricated using CAD-CAM technology where an intraoral scanner (IOS) is used to register the preparation, designed, and then milled from a material of choice.…”
mentioning
confidence: 99%